PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI â€œAFIKAâ€ UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI IMPULS DAN MOMENTUM - Nauly Rahmaniyah; Mita Anggaryani (PendIPA Journal of Science Education, 2023)
This research developed learning media based on animated videos, namely AFIKA. AFIKA specifically focuses on impulse and momentum as a learning topic. This study proposes to enhance student learning outcomes and confirm the feasibility of applying AFIKA in class. This study describes the validity assessment, the evaluation of learning implementation using AFIKA, and the learning evaluation results obtained from the pre-test and post-test assessments. This study applied the PIE development model, which comprises three stages: Plan (planning), Implementation (implementation), and Evaluate (evaluation). Data was collected through the expertise of validators to determine the validity of the media; Observers were responsible for monitoring and evaluating the implementation of learning activities in the classroom; Students provided feedback through response questionnaires, and their performance was assessed through pre-test and post-test evaluations. This study got 32 students from class X-3 of One of the Islamic High Schools in Gresik as the participants. The research instrument utilized a Likert scale to measure the scores. The findings of the conducted development research indicate that the AFIKA media, focusing on the topics of impulse and momentum in physics, achieved a validity score of 98.99% across material, media, and language aspects, indicating a high level of validity. Implementing learning activities using AFIKA media in class X-3 was highly successful, achieving a percentage of 98.66%. The overall response from students towards AFIKA media was positive. There was an improvement in the learning outcomes of class X-3 students in the physics of impulse and momentum after the implementation of AFIKA media, with an average N-Gain of 0.288, indicating a low level of improvement. The results suggest that AFIKA's animated video media on impulse and momentum material is practical and suitable for implementation. However, it may have a limited impact on increasing learning outcomes, which various factors could influence.